Delonix regia Leaf Extract (DRLE): A Potential Therapeutic Agent for Cardioprotection - Wang, Lung-Shuo (PLoS One, 2016)
Delonix regia (Boj. Ex. Hook) is a flowering plant in the pea family found in tropical areas and its leaves are used informally to treat diseases in folk medicine. However, the cardioprotective effects in this plant are still unclear. In this study, we found that the Delonix regia leaf extract (DRLE) (400 mg/kg/d) can reduce the mortality rate in an isoproterenol (ISO)-induced heart injury and hypertrophy mouse model. Decreased serum levels of creatine phosphokinase, LDH, GOT, TNF-alpha and increased nitric oxide levels were found in DRLE-treated ISO-injured mice. In the in vitro study, the porcine coronary artery exhibited vasodilation effect induced by DRLE in a dose-dependent manner. In the DRLE toxic test, overdose of DRLE showed the high safety in normal mice and may have the ability to remove the metabolic wastes in blood. In conclusion, we demonstrated for the first time that DRLE has the cardioprotective effects by activating the vasodilation through NO pathway and preventing the myocyte injury via inhibition of TNF-alpha pathway. We suggest that DRLE may act as a promising novel herbal medicine for cardioprotection.